Otolaryngology specialty choice among the 4th year MBBS students - Mumtaz Ahmad Umar, Mohibullah Mushwani, Naveed Arshad, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The discipline of otorhinolaryngology specialty is a very promising field all over the globe. This field is equipped with modified lifestyle as compared to general surgery field. However, otolaryngology is a flexible, promising and important field but still its trend is decreasing all over the world across the undergraduate’s professionals. Aim: To determine the frequency of otolaryngology specialty choice being taken by 4th year MBBS students. Methods: A descriptive cross-sectional study was conducted in otorhinolaryngology department of Islamabad Medical and Dental College, Islamabad from January to December 2020. The answers were obtained through the Likert scale-5 having the following components, as strongly agree, agree, not sure, disagree, strongly disagree. Results: A 100 undergraduate students participated in this survey. All students were of 4th year MBBS. 20% students were agreed and 40% not sure about the question regarding taking up otorhinolaryngology as a career choice and 15% strongly agreed for this. Conclusion: The study concluded that the graduates are not sure whether they want to choose otorhinolaryngology as their final career choice. We suggest that it should be one of the compulsory rotations during the internship. Keywords: Otorhinolaryngology; Specialty; Undergraduate medical education; Postgraduate; Career choice.